PENGARUH RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUB-SEKTOR INDUSTRI SEMEN YANG TERDAFTAR DIBURSA EFEK INDONESIA (BEI)PERIODE 2018-2023 - Jamila; Tati Herlina; Mailani Rabiulkhri (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2026)
The Influence of Return on Asset (ROA) and Return on Equity (ROE) on Stock Prices of Cement Industry Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2018–2023 Period. Supervised by Tati Herlina, S.E., M.Si. and Mailani Rabiulkhir, S.E., M.Si.This study aims to analyze the influence of Return on Asset (ROA) and Return on Equity (ROE) on Stock Prices of manufacturing companies in the cement industry sub-sector listed on the Indonesia Stock Exchange for the 2018–2023 period. The sample consisted of 6 companies observed over a six-year period. The analysis method used was panel data regression.The analysis results showed the regression equation Y = 4315.486 – 2.019824 X1 – 0.053500 X2. Partially, the Return on Asset (ROA) variable (X1) with a t_value > t_table or -0.024641 > -2.03452 indicates that ROA does not have a significant effect on Stock Prices. The Return on Equity (ROE) variable (X2) with a t_value > t_table or -0.005218 > -2.03452 also indicates that ROE does not have a significant effect on Stock Prices. However, based on the F-test, the F_value>F_table or 31.53063 > 3.28, which means that ROA and ROE simultaneously have a significant effect on Stock Prices.The coefficient of determination (R²) of 0.887389 indicates that 88.73% of the variation in Stock Prices can be explained by the ROA and ROE variables, while the remaining 11.27% is explained by other variables outside the model, such as Sales, Current Ratio, and Inflation (Sukartaatmadja et al., 2023).